Research and Application Progress of Field Modulation Magnetic Gear Transmission Technology - Liu Ruixia; Luo Shuai; Wu Xianfeng; Wang Jinzhong; Lu Yanghui; Liu Wei (Jixie chuandong)
The field modulation magnetic gear transmission technology is based on the principle of field modulation to achieve efficient and contactless transmission, effectively improving the problems of low torque density and low transmission ratio caused by the low utilization of magnets in traditional magnetic gears. It is expected to replace mechanical gear transmission devices for promotion and application. The working principle of field modulation magnetic gears was introduced, field modulation magnetic gears were classified from the perspective of topological structure, and the structural characteristics and transmission performance of different types of modulation magnetic gears were compared. The application progress of field modulation magnetic gears was analysed and summarized in the field of the variable speed transmission.